Three essays on labor, gender and development - Sedai, Ashish Kumar, author; Vasudevan, Ramaa, advisor; Pena, Anita Alves, advisor; Miller, Ray, committee member; Bhattarai, Niroj, committee member; Kroll, Stephan, committee member (Colorado State University. Libraries, 2022)
In my PhD dissertation, I write three research essays on labor, gender and development in India. These essays are based on applied economic research and use longitudinal data estimation techniques. These essays relate to my overall interest in topics surrounding inadequate access to basic infrastructures–electricity, water and credit–and their impact on gender inequities, development opportunities, health, education and labor force participation in India. The first essay focuses on informal finance and women empowerment from an economic and non-economic standpoint. The second essay examines reliable electrification and gender differences in employment, health and household decision making. The third chapter discusses access to piped water and gender differences in employment, health, education and household decision making. The first essay titled, Friends and Benefits? Rotating Savings and Credit Associations as Alternative for Women's Empowerment in India, co-authored with Ramaa Vasudevan and Anita Alves Pena, builds on a theoretical model of Rotating Savings and Credit Associations (ROSCAs). In informal social and financial organizations like ROSCAs, members contribute to a common pot of money that is awarded to a different member at each meeting randomly or through a bid. This study examines the effects of ROSCA on women's socio-economic freedom and autonomy at the national level in India. We compare ROSCAs to agency based micro-credit schemes and analyze their effects using nationally representative longitudinal gender-disaggregated data from 2005-2012. Building on a theoretical model of household savings and spousal bargaining power, we use individual fixed effects and instrumental variable regressions to test the theoretical predictions. Among others, results show that ROSCA membership increases the likelihood of women's cash in hand for expenditure by 1.7 percentage points, say in major purchase decisions by 3.9 percentage points and fertility choice by 4.7 percentage points. These margins exceed those for exogenous micro-credit schemes and are robust to sensitivity tests. This study is the first to contrast ROSCAs with other micro-credit schemes at the national level. We propose scaling up and associating longstanding ROSCAs with self-help groups for more inclusive development. The second essay titled, Does Reliable Electrification Reduce Gender Differences: Evidence from India, co-authored with Ramaa Vasudevan, Anita Alves Pena and Ray Miller, looks at the issue of the lack of reliable electrification in India despite massive improvements in electricity access in the past decade. We argue that reliable electricity could reduce the time allocated to home production thereby increasing labor market participation, more for women than men. This essay is purely empirical in nature and revolves around the issue of electrification and gender differences in India. We analyze the effect of quality of electricity on gender differences using a comprehensive set of labor and non-labor market outcomes in India viz. labor force participation (usual status and usual principal status of employment), fuel and water collection, decision making for women and choices of fuel and energy for the household. Using the temporal variation in household electricity hours from the India Human Development Survey (2005-2012), we use individual fixed effects and instrumental variables regressions. Our analysis reveals contrasting trends with significant progress at the extensive margin of electricity access, but little progress at the intensive margin of quality, hours of electricity. We find that reliable electrification improves socio-economic status of women relative to men through increased employment opportunities and reduced time allocation to home production. For instance, 10 more hours of electricity increases the likelihood of employment in the 'usual status' by 2.1 pp for men, and 3.9 pp for women. The study recommends considering electricity as a right, and as part of the broader strategy for reducing gender disparities in India. The third essay titled, Who Benefits from Piped Water? Evidence from a Gendered Analysis in India looks at the effect of access to piped water on employment in farm work, wage/salary work, work days, earnings, health and education outcomes by gender in India. Developing countries, including India, have made impressive progress in providing households with piped water in the last two decades. Yet, access and quality of water available for daily use remains very low. Given the disproportionate burden of home production, the 'hidden' agricultural labor of women, and the fact that India has inadequate access to clean water for daily use, intra-household labor and health inequality could be larger in the absence of piped water access. The disproportionate burden on women of water collection and distribution in the household in developing economies calls for a study on the relationship between piped water supply and gender differences in employment, women's health, child health and education. I use spatiotemporal data from the largest gender disaggregated human development survey in India, 2005–2012, and carry out econometric analyses using individual fixed effects, village fixed effects and instrumental variable regressions to evaluate the effects. Results show that household access to piped water increases the likelihood of wage/salary employment by 11 percent, and annual earnings increase by 14 percent for women, comparatively higher than men, but only in rural areas. In urban areas, there is no effect of pipe water on women's employment. With piped water, women's self-reported health improves; child's health and education outcomes also improve. The study recommends evaluating the social demand curve for piped water supply, and the consideration of piped water supply as necessity, as part of a broader strategy to reduce gender differences and minimize poverty. Overall, these essays are motivated by the lack of emphasis and policy action on micro-credit and basic infrastructures for the poor and the disadvantaged, especially in rural India. Therefore, all three papers in this dissertation provide policy recommendations to problems of India's economic development relating to gender inequity, marginalization, unemployment, education and health, which thread the three essays together.